Role of Child Friendly Environment in English Language Teaching - Subedi Bastola, Susmita (Kalika Journal of Multidisciplinary Studies, 2025)
This study investigates the role of child-friendly environments in English Language Teaching (ELT) in Nepalese community schools. A descriptive survey research design was employed, drawing data from both primary and secondary sources. The sample consisted of 25 teachers and 25 students selected through non-random sampling. Data were collected using questionnaires and interviews, and analyzed descriptively with the support of frequency tables, means, and standard deviations. The findings revealed that child-friendly environments enhance English learning by fostering active participation, reducing fear, and promoting learner-centered teaching. However, schools face challenges such as limited resources, economic constraints, lack of teacher training, and insufficient parental support. The study concludes that effective ELT in Nepalese schools requires strengthening physical infrastructure, teacher training, and inclusive practices. These findings provide insights for policymakers, curriculum designers, and school administrators in improving the quality of ELT through child-friendly environments.